PENGARUH IKLIM ORGANISASI, KEMAMPUAN KERJA DAN SEMANGAT KERJA TERHADAP KINERJA PEGAWAI DINAS PERIKANAN KABUPATEN BALANGAN - Machyulenny Fitriah; Rediyono Rediyono (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
This study aims to determine the organizational climate, work ability, and work spirit that can affect the performance of the employees of the fisheries service office of Balangan Regency. The data collected from questionnaires that were distributed directly of the fisheries service office of Balangan Regency. The result of this study showed that all independent variables have a positive influence on the performance of the employees of the fisheries service of Balangan regency, both individually and collectively so that the community gets good service from the employees